A history of word-formation in the Sanskrit grammars between Roth (1660-1668) and Bopp (1827) (Atti del Sodalizio Glottologico Milanese, 2024)
As is well-known, the descriptive grammars of the European languages started to regularly include a chapter on word-formation after Bopp’s work (Lindner 2015). However, the grammars of the Semitic languages, the philosophical grammars of German, the grammars of Sanskrit and some missionary grammars include such chapter even before Bopp. Among these, the German grammars were subject to some recent studies (Alfieri 2018, 2019), while the remaining groups of grammars have never been discussed in this perspective. The present paper aims to fill the gap by analysing the treatment of word-formation in the grammars of Sanskrit written before Bopp (1827).